1995
DOI: 10.1128/jvi.69.11.6697-6704.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection induces high levels of cyclins, phosphorylated Rb, and p53, leading to cell cycle arrest

Abstract: Human cytomegalovirus (HCMV) infection stimulates cellular DNA synthesis and causes chromosomal damage. Because such events likely affect cellular proliferation, we investigated the impact of HCMV infection on key components of the cell cycle. Early after infection, HCMV induced elevated levels of cyclin E, cyclin E-associated kinase activity, and two tumor suppressor proteins, p53 and the retinoblastoma gene product (Rb). The steady-state concentration of Rb continued to rise throughout the infection, with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
138
2
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(162 citation statements)
references
References 81 publications
21
138
2
1
Order By: Relevance
“…In our study, changes in cyclin D1 expression were not detected after infection, suggesting that the majority of the infected cells do not return to G1 phase after infection, as would be expected with normal cycling and division. In support of our findings, Jault et al [11] reported HCMV-induced G2/M arrest in cycling cells and found that high levels of cyclin E were induced, with cyclin A appearing only at late time points. De Bolle and coworkers [5] also reported that cyclin B1, cyclin A, and to a slight extent, cyclin E accumulated after HHV-6A infection in cord blood mononuclear cells.…”
supporting
confidence: 92%
“…In our study, changes in cyclin D1 expression were not detected after infection, suggesting that the majority of the infected cells do not return to G1 phase after infection, as would be expected with normal cycling and division. In support of our findings, Jault et al [11] reported HCMV-induced G2/M arrest in cycling cells and found that high levels of cyclin E were induced, with cyclin A appearing only at late time points. De Bolle and coworkers [5] also reported that cyclin B1, cyclin A, and to a slight extent, cyclin E accumulated after HHV-6A infection in cord blood mononuclear cells.…”
supporting
confidence: 92%
“…in the HHV-6A-infected condition, but this e¡ect was not maintained at later time points. These ¢ndings contrast with the HCMV-induced G 2 /M arrest in cycling cells, where induction of high levels of cyclin E was reported and cyclin A appeared only at late time points [19].…”
Section: E¡ect Of Hhv-6 Infection On Selected Cell Cycle Protein Exprcontrasting
confidence: 67%
“…HCMV-infected fibroblasts were elsewhere shown to undergo cell cycle arrest (Jault et al, 1995;Dittmer and Mocarski, 1997). This was evidenced by increased levels of cyclin-dependent kinase 2 (cdk2), cyclin E, and proliferating cell nuclear antigen (PCNA), as well as cellular DNA levels consistent with a block at either G 1 /S or G 2 /M (Jault et al, 1995;Dittmer and Mocarski, 1997). Cell cycle arrest was reproduced in cells transfected with IE2-86 (Wiebusch and Hagemeier, 1999).…”
Section: Effects Of Flavonoids Upon Hcmv Induction Of Cell Cycle Regumentioning
confidence: 99%